Malaysian Listed Firm’s Tax Avoidance: Another Earnings Management Strategy? - Mohd Razali, Mohd Waliuddin; Pong, Xiang Yi; Brahmana, Rayenda Khresna; Akmal Hisham, Tak (Human Resource Management Academic Research Society, 2019)
This study examines the role of tax avoidance on firm’s earnings management for a sample of 149 listed public firms in Malaysia over 2009 – 2013. Beneish M-score is used to measure the earnings management and effective tax rate to measure the tax avoidance. After controlling firm size, growth, leverage and profitability, the result shows that only two variables which tax avoidance and growth are positively significant towards the earnings management. The result implies that firms may manage their earning to enjoy tax advantages. Moreover, management in growth firms tend engages better earnings performance and thus it may affect the firm investment strategies.